Pengaruh Pemberian Pupuk Kompos Berbahan Dasar Guano dengan Level Berbeda terhadap Pertumbuhan Turi (Sesbania grandiflora) - Felix Bukifan; Stefanus Sio; Gerson F. Bira (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2019)
The abstracts represent all of the writing material and its implications, written briefly (about 200-250 words). A concise and factual abstract is required. The abstract should state briefly the purpose of the research, the principal results and major conclusions. An abstract is often presented separately from the article, so it must be able to stand alone. For this reason, References should be avoided, but if essential, then cite the author(s) and year(s). Also, non-standard or uncommon abbreviations should be avoided, but if essential they must be defined at their first mention in the abstract itself.Abstract should commence with a clear introduction of two or three sentences mentioning background of research. Subsequently, state the general problem of the research, followed by results/main findings that directly answer the problem. Give one or two sentence(s) to discuss the finding(s) or prospective(s).